Effects of Fractional CO2 Laser Treatment on Subglottic Scar in a Rabbit Model. (8th December 2020) - Marvin, Kastley; Schwartz, Isaac; Utz, Edward; Wilson, Justin; Johnson, Christopher; Gaudreau, Philip
Abstract : Objective: The objective of this study was to investigate the effects of fractional CO2 laser on subglottic scar. Study Design: Randomized controlled animal study. Setting: Academic medical center. Methods: Subglottic scar was induced in 12 New Zealand white rabbits via an endoscopic brush technique. This was followed by an open airway surgery that included vertical division of the cricoid and proximal trachea. Eight rabbits underwent fractional CO2 laser treatment of the scar via a Lumenis Ultrapulse Deep FX handpiece. Four rabbits underwent the open surgical approach without laser treatment. Bronchoscopy was performed at weeks 1, 2, 4, and 8. The animals were euthanized and laryngotracheal complexes harvested 12 weeks postsurgery. Immunohistochemistry was performed to determine the collagen composition of treated and untreated scars. Results: All 12 subjects survived to the study endpoint with no significant respiratory complications, despite 10 of 12 developing some degree of lateral tracheal narrowing. The median ratio of type I collagen to type III collagen in the laser group (1.57) was significantly more favorable than that of the untreated group (2.84; P =. 03). Conclusion: Treatment with fractional CO2 laser appears to have similar effects on subglottic scars as with cutaneous scars, improving the ratio of type I to type III collagen. Additionally, we developed an open airway approach in the rabbit model to deliver fractional CO2 laser treatment to the subglottis without introducing respiratory complications or compromising survival.